S91 A randomised, double-blind, placebo-controlled crossover study to assess the efficacy of a single dose of 100 mg of VRP700 by inhalation in reducing the frequency and severity of cough in adult patients with Idiopathic Pulmonary Fibrosis. (12th November 2015) - Satia, I; Badri, H; Dockry, R; Chaudhuri, N; Brown, G; Abbott-Banner, K; Smith, JA
Abstract : Background: Cough is a common, troublesome symptom in idiopathic pulmonary fibrosis (IPF), but the underlying mechanisms are poorly understood and effective therapies are lacking. VRP700 is thought to inhibit ion-channels found on sensory afferents innervating the airways. We aimed to investigate the efficacy of VRP700 in reducing cough frequency in patients with IPF. Method: A single centre double-blind randomised, placebo controlled crossover study in patients with IPF with chronic cough. Patients were randomised to receive a single inhaled dose of VRP700 (100 mg) or placebo and then crossed-over after a 7 day washout period. The primary endpoint was the number of coughs in the 4 h following the end of nebulisation for VRP700 compared with placebo, measured using an objective cough monitoring system (VitaloJAK, Vitalograph Ltd). Secondary endpoints included urge to cough visual analogue scale (VAS), cough severity VAS, and dyspnoea VAS, recorded at 1, 2 and 4 h post-dose, at the end of the day and 24 hrs post-dose. Results: Twenty five patients were screened, 5 were ineligible and therefore 20 were randomised [mean age 69.8(±6.9) yrs, 12 female, mean FEV1 1.97 ± 0.39 L, mean FVC 1.86 ± 0.42 L]. The geometric mean number of coughs in the 4 h following VRP700 treatment was significantly higher compared with placebo [136.8 (95% CI 80.3- 233.1) vs. 64.9 (95% CI 38.1–110.6), p < 0.001). There was no evidence of an order or period effect. The difference in cough counts was greatest during the first hour after VRP700 nebulization [63.3 (95% CI 36.4–109.8) vs. 24.1 (95% CI 13.9–41.9), p < 0.001). For reported cough severity, urge to cough, and dyspnoea severity scores there were no differences between VRP700 and placebo at almost all time-points, apart from the dyspnoea severity VAS at 24 h post-dose, where VRP700 was significantly better than placebo (p = 0.012). Conclusion: VRP700, administered by nebuliser as a single inhaled dose of 100 mg, did not reduced the frequency and severity of cough in IPF patients with troublesome cough. Instead the inhalation of VRP700 seemed to evoke coughing.